Equitable Distribution of Wealth and Resources in Islam - Salim, Ruhul (Routledge, 2016)
Fairness and justice are fundamental virtues in Islam. With respect to fair and equitable distribution of wealth and resources in Islam the analysis in this chapter follows the Tawhidi approach. Accordingly, the analysis shows that there are clear guidelines in Qur’an regarding the creation, possession and disposition of wealth. While lawful act of earning wealth is considered as worship unlawful way of acquiring wealth is forbidden in Islam. Importantly, justice in Islam incorporates three basic principles, namely ‘adl’, ‘insaf’ and ‘ihsan’. Hence, wealth should be earned, invested and spent in the correct avenues as per the spirit of Islam. Islam also provides a broad foundation of distribution of wealth and resources in order to establish peace, prosperity, justice, security and economic balance in the society.